Short‐ and Long‐Term Prognosis of Patients With Takotsubo Syndrome Based on Different Triggers: Importance of the Physical Nature - Aitor Uribarri; Iván J. Núñez‐Gil; D. Aritza Conty; Oscar Vedia; Manuel Almendro‐Delia; Albert Duran Cambra; Agustin C. Martin‐Garcia; Marisa Barrionuevo‐Sánchez; Manuel Martínez‐Sellés; Sergio Raposeiras‐Roubín; Marta Guillén; Jose Maria Garcia Acuña; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2019)
Background Takotsubo syndrome (TTS) is an acute reversible heart condition initially believed to represent a benign pathology attributable to its self‐limiting clinical course; however, little is known about its prognosis based on different triggers. This study compared short‐ and long‐term outcomes between TTS based on different triggers, focusing on various physical triggering events. Methods and Results We analyzed patients with a definitive TTS diagnosis recruited for the Spanish National Registry on TTS (RETAKO [Registry on Takotsubo Syndrome]). Short‐ and long‐term outcomes were compared between different groups according to triggering factors. A total of 939 patients were included. An emotional trigger was detected in 340 patients (36.2%), a physical trigger in 293 patients (31.2%), and none could be identified in 306 patients (32.6%). The main physical triggers observed were infections (30.7%), followed by surgical procedures (22.5%), physical activities (18.4%), episodes of severe hypoxia (18.4%), and neurological events (9.9%). TTS triggered by physical factors showed higher mortality in the short and long term, and within this group, patients whose physical trigger was hypoxia were those who had a worse prognosis, in addition to being triggered by physical factors, including age >70 years, diabetes mellitus, left ventricular eyection fraction <30% and shock on admission, and increased long‐term mortality risk. Conclusions TTS triggered by physical factors could present a worse prognosis in terms of mortality. Under the TTS label, there could be as yet undiscovered very different clinical profiles, whose differentiation could lead to individual better management, and therefore the perception of TTS as having a benign prognosis should be generally ruled out.